Domain 3 of NS5A protein from the hepatitis C virus has intrinsic α-helical propensity and is a substrate of cyclophilin A - Verdegem, Dries; Badillo, Aurélie; Wieruszeski, Jean-Michel; Landrieu, Isabelle; Leroy, Arnaud; Bartenschlager, Ralf; Penin, François; Lippens, Guy; Hanoulle, Xavier (The journal of biological chemistry, 2011)
Nonstructural protein 5A (NS5A) is essential for hepatitis C virus (HCV) replication and constitutes an attractive target for antiviral drug development. Although structural data for its in-plane membrane anchor and domain D1 are available, the structure of domains 2 (D2) and 3 (D3) remain poorly defined. We report here a comparative molecular characterization of the NS5A-D3 domains of the HCV JFH-1 (genotype 2a) and Con1 (genotype 1b) strains. Combining gel filtration, CD, and NMR spectroscopy analyses, we show that NS5A-D3 is natively unfolded. However, NS5A-D3 domains from both JFH-1 and Con1 strains exhibit a propensity to partially fold into an α-helix. NMR analysis identifies two putative α-helices, for which a molecular model could be obtained. The amphipathic nature of the first helix and its conservation in all genotypes suggest that it might correspond to a molecular recognition element and, as such, promote the interaction with relevant biological partner(s). Because mutations conferring resistance to cyclophilin inhibitors have been mapped into NS5A-D3, we also investigated the functional interaction between NS5A-D3 and cyclophilin A (CypA). CypA indeed interacts with NS5A-D3, and this interaction is completely abolished by cyclosporin A. NMR heteronuclear exchange experiments demonstrate that CypA has in vitro peptidyl-prolyl cis/trans-isomerase activity toward some, but not all, of the peptidyl-prolyl bonds in NS5A-D3. These studies lead to novel insights into the structural features of NS5A-D3 and its relationships with CypA.